Syntactic Analysis of Sentence Structures in Bussiness Letters by The Fifth Semester Students of Letters Faculty of UMI Makassar - Burhanuddin Burhanuddin; Emma Bazergan; Tasman Buton (Fakultas Sastra - Universitas Muslim Indonesia, 2018)
This Research aimed to find out the constructions of Sentence Structure particularly in the fifth semester students’ assigments of bussiness letters. Besides that, this research also aimed to find out the errors of Sentenc Structure Constructions which made by the fifth semester students. This reseach used a descriptive method in order to describe and explain some constructions and errors which are made by the fifth semeseter students. The result of this research helps the students in learning English and the students can increase their ability in constructing sentence structure specially for their advance writing. Their writing can be more interesting with a complete sentence structure.